Multi-enzymatic complex in pig diet finishing - Biancalana, R. F.; Lima, M. O.; Cella, P. S. (Scientific Electronic Archives, 2018)
This study aimed to evaluate the effects of a multienzyme complex in pigs in the finishing phase on weight gain variables (WG), feed intake (FI), feed conversion (FC) and the cost of feed per animal kilogram produced. The additive used was a trademark consisting of phytase, protease, xylanase, B- glucanase, cellulase, amylase and Pectinase. 12 animals were distributed in a completely randomized design with two treatments (T1 - control treatment and T2 -Treatment with additive), three replicates and two animals per experimental unit. Performance data were submitted to analysis of variance, the difference between the average verified by test F. There was no effect (P> 0.05) of the treatments in the productive and economic parameters. Depending on the results, it is concluded that the addition of the enzymatic complex in swine diets in the finishing phase did not influence positively the economic and productive performance of the animals.